2013
DOI: 10.11604/pamj.2013.14.27.1925
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plasmodium falciparum and hookworm infections on the frequency of anaemia in pregnant women of rural communities in Enugu, South East Nigeria

Abstract: IntroductionMalaria and hookworm infections are common in sub-Saharan Africa and they increase the prevalence of anaemia in pregnancy with resultant poor pregnancy outcomes. This study was carried out to assess the impact of Plasmodium falciparum and hookworm infections on the frequency of anaemia among pregnant women in two rural communities in Enugu, South East Nigeria.MethodsA cross sectional descriptive study was carried out in a total of 226 women attending antenatal clinics at two rural Primary Health Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…This study has also shown that participants with parasitic infections such as malaria and intestinal parasites (intestinal flagellate, S. mansoni , and S. haematobium ) were more anaemic ( Table 3 ), though the difference was not statistically significant. This is in contrast to a study by Agu et al [ 24 ] who observed a significant association between parasitic infection and anaemia among pregnant women. Majority of women with anaemia were from the rural settlement and the presence of intestinal parasite and malarial infection could have contributed to the anaemia.…”
Section: Discussioncontrasting
confidence: 99%
“…This study has also shown that participants with parasitic infections such as malaria and intestinal parasites (intestinal flagellate, S. mansoni , and S. haematobium ) were more anaemic ( Table 3 ), though the difference was not statistically significant. This is in contrast to a study by Agu et al [ 24 ] who observed a significant association between parasitic infection and anaemia among pregnant women. Majority of women with anaemia were from the rural settlement and the presence of intestinal parasite and malarial infection could have contributed to the anaemia.…”
Section: Discussioncontrasting
confidence: 99%
“…Not surprisingly, children were at highest risk, which is in line with previous studies conducted in Kenya [ 45 ], Nigeria [ 46 ] and Cameroon [ 47 ]. The association between Plasmodium infection and anaemia supports the finding that malaria plays a major role in the occurrence of anaemia in tropical areas [ 48 50 ]. Nevertheless, other causes cannot be excluded.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, even with relatively good antenatal care, treatment was not initiated until the second trimester at which time anemia was prevalent in this cohort. Furthermore, unlike the region where this study was conducted and despite the international recommendations, uptake of treatment for hookworm, malaria, and schistosomiasis in ANC is still low in many parts of Africa [40], [56]. In part, this may relate to perceptions that treatment has not been associated with improved pregnancy outcomes [38], or may be harmful [40].…”
Section: Discussionmentioning
confidence: 91%
“…Parasitic infections, including hookworm, may be evaluated by intensity of infection, as measured by the concentration of eggs in the stool [25] . While most morbidity has been seen with high intensity infections, in populations with low iron stores, even low-intensity hookworm infection has been associated with morbidities [25] – [30] . In addition to hookworm, P. falciparum malaria increases risk for moderate and severe maternal anemia [11] [16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation